Current transformer modeling for compensating algorithms - (:unkn) unknown (My University, 2013)
This work is about modeling and compensating CT's secondary current during saturation since working condition of the protection devices such as differential and impedance relays is mostly affected by the operating condition of the CTs. Saturated secondary currents depending on the magnitude of the fault current and remnant flux in magnetic core can cause incorrect operation or operating time delay of protective relays. Therefore, relay experts should take account of the CT saturation problem when they design a protective relay, especially a current differential relay. The objective of this paper is to propose an effective way of CT modeling based on transmission line method (TLM) with Jiles-Atherton technique for correcting secondary current of CT under saturation. © 2013 IEEE.
Keywords: current transmormer; Jiles-Atherton; modeling; TLM